Scientific school of Russian and Ukrainian studies at the Belarusian State University - Yanouski, Aleh A.; Menkouski, Viachaslau I. (Journal of the Belarusian State University. History, 2022)
The process of formation and development of Russian and Ukrainian studies at the Belarusian State University as a scientific historical discipline and educational course is analysed. It is noted that since the 1936/37 academic year it is possible to find a documented trace of the continuity in the study and the teaching of the discipline at the level of special educational and scientific structures: the department of the history of the peoples of the USSR and the history of the BSSR, department of the history of the peoples of the USSR, department of history of the USSR, department of history of the USSR of the pre-Soviet period, department of the history of the USSR of the era of socialism, department of contemporary history of Slavic countries (based on this department of the history of the Southern and Western Slavs was created), department of Russian history (which was formed on the basis of the department of history of the USSR of the pre-Soviet period, was transformed first into the department of Russian and Slavic history, and then into the modern department of Russian history). The author notes the relationship between the development of Russian studies and Ukrainian studies as a direction of historical knowledge with the socio-political situation in the country, the role of historians of the Belarusian State University in the formation of the national structure of historical memory, understanding the importance of historical science for society and the state. The national Belarusian historiography is characterised as a significant component of the European historiography of the history of Russia and Ukraine, its integration into the general European scientific process of studying countries and regions. The prospects for the development of Russian and Ukrainian studies in Belarus at the present stage, the expansion of the process of interdisciplinary synthesis in the late 20th – early 21th centuries are considered. The conclusion is made about the transformation of Russian studies and Ukrainian studies into one of the leading areas of modern historical science, which is part of the complex of social and humanitarian scientific disciplines.